FAKTOR-FAKTOR YANG MEMPENGARUHI USAHATANI PADI SAWAH DI DESA NOELBAKI KECAMATAN KUPANG TENGAH KABUPATEN KUPANG - Fitriyani, Fitriyani; Bernadina, Lika; Darlen, Maria Fransiska (Buletin Ilmiah Impas, 2023)
This research was conducted in Noelbaki Village, Central Kupang Subdistrict, Kupang Regency in October - November 2022, with the aim of knowing the productivity, income and factors affecting productivity and income of paddy rice farming in Noelbaki Village, Central Kupang Subdistrict, Kupang Regency. The selection of the research location was carried out purposively with the consideration that Noelbaki Village is a producer of paddy rice with the largest land area in the Central Kupang sub-district. The research sample was taken with the Simple Random Sampling technique, where there were 3 farmer groups, namely, the Dendeng farmer group totaling 345 members, the Joint Business farmer group totaling 220 members and the Dahulu Rasa farmer group totaling 180 members using a 10% error rate which took 75 respondents. The results showed that the productivity of rice farming ton/ha is still far from the national average productivity of 8 tons/ha. The income of paddy rice farming in Noelbaki Village obtained an average income of Rp 22,315,343. While partially or individually, the variable Farming Experience (X1), variable Land Area (X5), and Pesticides (X8) partially affect the productivity of rice paddy farming in the village. The variables that affect the income (Y2) are, variable Labor (X3), Cost (X4) and Land Area (X5).